Rancang Bangun Sistem Informasi Pembelian dan Penjualan Barang Berbasis Website (Studi Kasus: CV. Samdhika Elektronik Depok) - Dicky Hariyanto (Swabumi, 2016)
The need for rapid and accurate information is one of the factors the rapid development of informationtechnology in this era. Inevitably application of information technology in a company / institution is neededto enhance the effectiveness of work and cost efficiency of daily operations. CV. Electronic Samdhika Depok isa company engaged in the purchase and sale of electronic goods have not utilize information technology as awhole because the CV process. Electronic Samdhika Depok already use computers for activities of dailybusiness but have not yet implemented a computerized information system is integrated in the process ofbuying and selling goods. Therefore, the author intends to design and develop information systems purchasesand sales that could be useful for CV. Electronic Samdhika Depok as an improvement over the use ofinformation technology-based website with SDLC approach of using the waterfall model.Keywords: Development, Utilization, Information Technology